Optimalisasi Peran Humas Sekolah dalam Meningkatkan Citra dan Kepercayaan Publik di Era Digital - Putri, Azzahra Dwi Maulani; Putri, Gayasal Agisni; Maharani, Nadia Fitri; Sofiyani, Navisa Elsofa; Prihantini, Prihantini (Indo-MathEdu Intellectuals Journal, 2025)
The development of information and communication technology in the digital era has transformed how schools build their image and public trust. School Public Relations (PR) plays a strategic role as a liaison between schools and the community, responsible for delivering information, maintaining reputation, and fostering mutual trust. This study aims to explore how school PR can optimize its role in the digital era. The research methods include interviews with PR practitioners, analysis of school social media activities, and document reviews related to communication policies. The findings reveal that social media plays a crucial role as the primary platform for building a school's image, enabling broader and more interactive communication with the community. Additionally, transparency in information dissemination is critical for enhancing public trust, particularly through effective and responsive crisis information management. The study concludes that mastering digital communication strategies, including social media literacy and information management, is essential for school PR professionals. This article also provides recommendations to enhance PR competencies, such as digital literacy training and the development of adaptive communication strategies, to address the challenges of the digital era.